A qualitative exploration of service users’ experiences of violence risk assessment and management in forensic mental health settings: an interpretative phenomenological analysis - Laithwaite, Heather (Journal of Forensic Psychology Research and Practice, 2022)
Violence risk assessment and management is central to the lives of forensic mental health service users. Whilst studies have explored mental health professionals’ experiences of violence risk assessment and management, research regarding service user views is largely absent from the literature. Using Interpretative Phenomenological Analysis, the current study interviewed seven forensic mental health service users in low secure mental health inpatient settings about their experi-ences of violence risk assessment and management. Interviews were recorded, transcribed, and analyzed. Results identified four superordinate themes; Who is this for?, Power, Misunderstood, and Moving Forward. The results are discussed in relation to existing literature. Clinical implications and future research directions are then considered.